2010
DOI: 10.1186/1824-7288-36-16
|View full text |Cite
|
Sign up to set email alerts
|

Serological screening for celiac disease in schoolchildren in Jordan. Is height and weight affected when seropositive?

Abstract: Background Celiac disease (CD) emerged as a public health problem, and the disease prevalence varies among different races. The present study was designed to investigate the prevalence of CD using serological markers in apparently healthy schoolchildren in Irbid City, Jordan. Additionally, the effect of positive serology on height, weight and body mass index (BMI) was evaluated. Methods The study population consisted of 1985 children (1117 girls and 868 boys), age range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…Fourteen studies were European, [67][68][69][70][71][72][73][74][75][76][77][78][79][80] two African 81,82 and one Asian. 83 The prevalence of positive IgA EMA, elevated IgA tTG levels and biopsy-positive CD in these studies ranged from 0.78% to 5.66%, 0.43% to 2.42% and 0.11% to 1.71% respectively. 81 In Saharawi, sub-Saharan Africa, 5.6% of 989 unselected children had elevated tTG levels and also tested positive for IgA EMA.…”
Section: Incidence and Prevalence Of Clinically Diagnosed CD (Tables mentioning
confidence: 66%
“…Fourteen studies were European, [67][68][69][70][71][72][73][74][75][76][77][78][79][80] two African 81,82 and one Asian. 83 The prevalence of positive IgA EMA, elevated IgA tTG levels and biopsy-positive CD in these studies ranged from 0.78% to 5.66%, 0.43% to 2.42% and 0.11% to 1.71% respectively. 81 In Saharawi, sub-Saharan Africa, 5.6% of 989 unselected children had elevated tTG levels and also tested positive for IgA EMA.…”
Section: Incidence and Prevalence Of Clinically Diagnosed CD (Tables mentioning
confidence: 66%
“…Eighteen studies included in this meta-analysis reported seroprevalence of CD in various Asian countries. [16][17][18][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] In these studies, 47 873 individuals were screened using anti-tTG ab and/or AEA, and 884 individuals were reported to be seropositive for CD. Hence, the pooled sero-prevalence of CD using anti-tTG ab and/or AEA in Asian countries was 1.6% (95% CI 1.1%, 2.0%) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Of 18 studies reporting sero-prevalence, intestinal mucosal biopsies were not performed in four of the studies; hence, they were excluded from estimating the pooled prevalence of CD. 32,33,40,41 Of 43 955 individuals screened in the remaining 14 studies, 809 individuals were seropositive for CD using anti-tTG ab and/or AEA. [16][17][18][29][30][31][34][35][36][37][38][39]42,43 Of them, 344 (42.5%) individuals did not undergo duodenal biopsies.…”
Section: Resultsmentioning
confidence: 99%
“…Esophagogastroduedinoscopy and biopsy was done in Alsalam General Hospital in Mosul city where three sites of duodenum were biopsied from every patient. Biopsy specimens were evaluated in the same hospital and pathology reports were analyzed according to Marsh criteria (4) .…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence of celiac disease in Tunisian schoolchildren, estimated to be about 1/157 which is close to the European prevalence (2) . In Jordan the serological prevalence was estimated to be 1:124 in schoolchildren (4) , whereas the average annual incidence in Kuwait is 1:3000 (5) . To date no prevalence of celiac disease data were reported from Iraq.…”
mentioning
confidence: 99%